KEMAMPUAN SISWA KELAS VII SMP PLUS AT-THOIBA KOTA PEKANBARU T.A 2013/2014 DALAM MEMBACA CEPAT - Nazirun Nazirun; Hermaliza Hermaliza; Diah Setyorini (UIR Press, 2014)
Reading is an important activity, they are a fast readingandsilent reading. To boost reading skills one of them is fast reading. The problem of this research is how much the speed reading of class VII SMP PLUS AT-THOIBA Pekanbaru AcademicYear 2013/2014. How students class VII PLUS ATTHOIBA Pekanbaru academic year 2013/2014 in speed reading. This study aims to describe, analyze, interpret ability of the student class VII PLUS AT-THOIBA Pekanbaru academic year 2013/2014 in speed reading. The population is full sample comprised 28 students of class VII PLUS AT-THOIBA. This research method is descriptive method with quantitative approach. The theory used is Henry Guntur GM (1986), Abdul Razak (2005), Tampubolon (2008), Dalman (2010), Sudirman (2010), Nurgiantoro (2011). Analysis using the formula based on Tampubolon research, and evaluation criteria based SBC (2007) The results of the research capabilities of the first hypothesis stated that speed reading at class VII SMP PLUS AT- THOIBA Pekanbaru academic year 2013/2014 city in fast reading is low with less speed 60-90 wpm and students read high category is 104 wpm. The second hypothesis states that the reading ability of students of class VII PLUS AT-THOIBA Pekanbaru academic year 2013/2014 in fast reading is enough to 50-69 with less categoriy. It is shownthat the average of students’ ability who obtained 80. As summary,fast reading at class VII SMP PLUS AT- THOIBAPekanbaru academic year 2013/2014 is high category with 104 wpm, and the ability of the student class VII PLUS AT-THOIBA Pekanbaru academic year 2013/2014 is quick fast in reading category.